An evolutionarily conserved role for CTNNB1/β-CATENIN in regulating the development of the corpus callosum - Arpan Parichha; Debarpita Datta; Amrita Singh; Ishita Talwar; Shreya Yadav; Mahima Bose; Varun Suresh; Špela Miroševič; Nina Žakelj; David Gosar; Damjan Osredkar; Shubha Tole (iScience)
Summary: The corpus callosum (CC) is a major nerve bundle that connects the two hemispheres of the brain. Dysgenesis of the CC is associated with neurodevelopmental disorders such as the CTNNB1 syndrome. We identified that five individuals carrying CTNNB1 mutations displayed CC deficits. To explore CTNNB1/β-CATENIN-dependent mechanisms that regulate CC midline crossing, we examined mice with Ctnnb1 gain of function (GOF) or loss of function (LOF) selectively targeted to the early embryonic central nervous system midline using an Lmx1aCre driver. We identify that the Lmx1a lineage contributes to midline cell populations known to regulate CC pathfinding: the glial wedge, the indusium griseum glia, and a population of midline glutamatergic neurons. We find that each of these structures are affected in both GOF and LOF embryos, resulting in a profound disruption of CC crossing and formation of Probst bundles. Thus, regulated β-CATENIN function in midline cell populations is critical for CC development, and its dysregulation may underlie the CC deficits associated with CTNNB1 syndrome.